2015
DOI: 10.1371/journal.pgen.1004921
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Suppressor BCL7B Functions in the Wnt Signaling Pathway

Abstract: Human BCL7 gene family consists of BCL7A, BCL7B, and BCL7C. A number of clinical studies have reported that BCL7 family is involved in cancer incidence, progression, and development. Among them, BCL7B, located on chromosome 7q11.23, is one of the deleted genes in patients with Williams-Beuren syndrome. Although several studies have suggested that malignant diseases occurring in patients with Williams-Beuren syndrome are associated with aberrations in BCL7B, little is known regarding the function of this gene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 94 publications
6
39
0
1
Order By: Relevance
“…Bcl7 gene family consists of Bcl7A, Bcl7B , and Bcl7C . Uehara T et al found that Bcl7 was required for normal seam cell development in Caenorhabditis elegans . Furthermore, Bcl7 knockdown suppressed KATOIII human gastric cancer cell death and regulated the Wnt‐signaling and apoptotic pathways .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bcl7 gene family consists of Bcl7A, Bcl7B , and Bcl7C . Uehara T et al found that Bcl7 was required for normal seam cell development in Caenorhabditis elegans . Furthermore, Bcl7 knockdown suppressed KATOIII human gastric cancer cell death and regulated the Wnt‐signaling and apoptotic pathways .…”
Section: Resultsmentioning
confidence: 99%
“…Uehara T et al found that Bcl7 was required for normal seam cell development in Caenorhabditis elegans . Furthermore, Bcl7 knockdown suppressed KATOIII human gastric cancer cell death and regulated the Wnt‐signaling and apoptotic pathways . So, Bcl7A may play an important role in the development of BmN cells.…”
Section: Resultsmentioning
confidence: 99%
“…[1,12] BCL7B, another Wnt pathway tumor suppressor gene located on WBSCR, could also contribute to malignancy in patients with WBS. [13] Such genes, together with others involved in DNA repair (e.g., RFC2), could have a role in WT tumorogenesis. In this regard and due to inconclusive evidence of concordance for WT in twins, [14] we follow both twins regularly.…”
Section: Letter To the Editor Twins With Williams-beuren Syndrome Andmentioning
confidence: 99%
“…identified possible Wnt pathway target genes in WT tumorogenesis, including FZD9 , positioned on WBSCR . BCL7B, another Wnt pathway tumor suppressor gene located on WBSCR, could also contribute to malignancy in patients with WBS . Such genes, together with others involved in DNA repair (e.g., RFC2), could have a role in WT tumorogenesis.…”
mentioning
confidence: 99%
“…BCL7A belongs to the BCL7 family, which includes BCL7B and BCL7C , and is a known pro-apoptotic tumor suppressor in B-cell oncogenesis. Specifically, BCL7B suppresses β-catenin expression, causing Wnt signaling inhibition [7]. Importantly, β-catenin deregulation in Wnt signaling is associated with genomic instability that can induce oncogenic translocations in T-cell lymphoma and AML [58].…”
mentioning
confidence: 99%